Susceptibility to Scams in Older Black and White Adults - Han, S. Duke; Barnes, Lisa L.; Leurgans, Sue; Yu, Lei; Stewart, Christopher C.; Lamar, Melissa; Glover, Crystal M.; Bennett, David A.; Boyle, Patricia A. (Frontiers in Psychology, 2021)
Previous reports on racial differences in scam susceptibility have yielded mixed findings, and few studies have examined reasons for any observed race differences. Older Black and White participants without dementia (N=592) from the Minority Aging Research Study and the Rush Memory and Aging Project who completed a susceptibility to scam questionnaire and other measures were matched according to age, education, sex, and global cognition using Mahalanobis distance. In adjusted models, older Black adults were less susceptible to scams than older White adults (Beta=-0.2496, SE=0.0649, p=0.0001). Contextual factors did not mediate and affective factors did not moderate this association. Analyses of specific items revealed Blacks had greater knowledge of scam targeting of older adults and were less likely to pick up the phone for unidentified callers. Older Black adults are less susceptible to scams than demographically-matched older White adults, although the reasons remain unknown.